Pengaruh Perbandingan Tepung Talas Beneng (Xanthosoma Undipes K.Koch) dan Tepung Kacang Merah (Phaseolus Vulgaris L.) terhadap Karakteristik Snack Bar - Dewi, Ni Made Nia Kartika; Putra, I Nengah Kencana; Wisaniyasa, Ni Wayan (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 13 No 2 (2024): Jurnal ITEPA, 2024)
Snack bars are practical and nutritious snacks. Generally, snack bars are made from various mixtures of flour and dry ingredients such as cereal, nuts, and dried fruit. The use of taro beneng and red bean flour in this research aims to tap into local food potential and enhance the nutritional value of the snack bar. The purposes of this research are to determine the effect of the taro beneng and red bean flour ratio on the characteristics of snack bars and to identify the optimal ratio for producing a high-quality snack bar. This study employed a Completely Randomized Design (CRD) with the treatment ratios of taro beneng and red bean flour, consisting of 5 levels as follows: 70%:30%; 60%:40%; 50%:50%; 40%:60%; 30%:70% with 3 replications for each, producing a total of 15 sample units. Analysis of Variance (ANOVA) was conducted, and if a significant effect was observed, the Duncan Multiple Range Test (DMRT) was used to analyze the data. The results demonstrated that the ratio of taro beneng flour to red bean flour significantly influenced the protein, water, ash, fat, carbohydrate, rough fiber, hardness, and the hedonic characteristics for aroma, taste, color, texture, and overall acceptance. The snack bar exhibiting the best characteristics was produced with a ratio of taro beneng and red bean flour of 50%:50%. This formulation yielded a snack bar containing 12.31% protein, 12.94% water, 2.64% ash, 17.22% fat, 53.89% carbohydrate, 5.99% rough fiber, and a hardness of 67.90 N. The overall acceptance of this snack bar was liked.